2001
DOI: 10.1209/epl/i2001-00182-9
|View full text |Cite
|
Sign up to set email alerts
|

Violation of the fluctuation-dissipation relation during the formation of a colloidal glass

Abstract: The relationship between the conductivity and the polarization noise is measured in a gel as a function of frequency in the range 1Hz − 40Hz. It is found that at the beginning of the transition from a fluid like sol to a solid like gel the fluctuation dissipation theorem is strongly violated. The amplitude and the persistence time of this violation are decreasing functions of frequency. At the lowest frequencies of the measuring range it persists for times which are about 5% of the time needed to form the gel.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
129
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 29 publications
10
129
2
Order By: Relevance
“…We measure the equal-time fluctuations of this local oscillator and show that, in an ergodic phase, the temperature of the oscillator T o equals the environment temperature T bath of the system, as required by equilibrium statistical mechanics. Significantly, when we repeat the measurements in an aging glass we find a higher temperature and T o > T bath .All experiments to date on colloidal glasses [3,4,5] have relied on active, driven measurements. We conduct our experiments instead in a quasi-static limit which has several advantages.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…We measure the equal-time fluctuations of this local oscillator and show that, in an ergodic phase, the temperature of the oscillator T o equals the environment temperature T bath of the system, as required by equilibrium statistical mechanics. Significantly, when we repeat the measurements in an aging glass we find a higher temperature and T o > T bath .All experiments to date on colloidal glasses [3,4,5] have relied on active, driven measurements. We conduct our experiments instead in a quasi-static limit which has several advantages.…”
mentioning
confidence: 61%
“…Experiments have so far produced conflicting results. Studies of colloidal glasses have reported that T eff increases [3], remains unchanged [4], or even decreases [5] with age in contrast to measurements on structural [6] and spin glasses [7] which have revealed effective temperature warmer than the bath temperature.In this Letter, we report the temperature of a micrometer-sized sphere immersed in an aging colloidal suspension, as the suspension transforms from a fluid to a glass. The particle, captured in an optical trap, constitutes a microscopic harmonic oscillator whose fluctuations probe the nonequilibrium dynamics of the aging glass.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although theoretical results have flourished, the difficulties in the experimental testing of the fundamental predictions of the theories have hampered the development of an understanding of ageing in glasses [14][15][16][17][18] . Experiments so far have shown conflicting results, which are usually masked by large intermittent fluctuations in the observables 17 ; a behaviour which seems beyond the current theoretical formalisms 2 .…”
mentioning
confidence: 99%